November Report: Department of Industrial Therapy - Henry L. Marshall::::::; Paul Komuro::::::
This primary document is a report in which the department of industrial therapy which stated that industrial therapists are assigned referred patients only on there two wards in the R&T Building. The reason for this change is to fix issues in the mental hospitals that need improvement such as:(1) Patients referral cards must be completely and accurately filled out by ward personnel. (2) Industries covered by the department should not accept any patients for work without a Referral card or verbal notification from this department. (3) Patients must be encouraged to fulfill their tasks in jobs unless they have been excused from duties due to illness, company, appointments with the ward physician. (4) Due to no Food service on weekends, patients have the option of weekend work with time off during the week. (5) Staff must submit monthly progress reports of patients.